(3QSGdI NGajI GdLaQ GdefShHI Edi MVQI GdEeGe LYaQ GdUGOb QVj Gddg JYGdi Yfgs
(3ChdgG (B:s
(3GHJOC cJGH NGajI GdMaQ hgh GdefShH Edi MVQI GdEeGe LYaQ GdUGOb QVj Gddg JYGdi Yfg s
(3BNQgG (B:s
(3hjdRec Cf JbQC GdaGJMI def hVY gPg GdCSeGA hCdagG hGdSdGe hUdi Gddg Ydi SjOfG eMeO hYdi hUMHg hSde JSdjekG cKjQkG hGdMeO ddg HcQI hCUjdkG Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQcR jI GdYGeI (B- (3GdehUd (B(300 (3L(B) s
Keywords: (3GdMQha h GdChaGbs